Быстродействующие электроприводы постоянного тока с широтно-импульсными преобразователями - Гольц М. Е. Марк Ефимович; Гудзенко А. Б. Александр Борисович; Остреров В. М. Владимир Михайлович; Шевченко Б. П. Борис Петрович; Шпиглер Л. А. Людвиг Александрович (Москва, Энергоатомиздат, 1986)
Авт. указ. на обороте тит. л.